Fatalism, Attributions of Failure and Academic Performance in Mapuche and Non-Mapuche Chilean Students - Otzen, Tamara; Betancourt, Hector; González-Plitt, María-Elena; Martella, Diana (Anales de Psicología / Annals of Psychology, 2016)
This study investigated the role of fatalism as a cultural value orientation and causal attributions for past failure in the academic performance of high school students in the Araucania Region of Chile. Three thousand three hundred and fourty eight Mapuche and Non-Mapuche students participated in the study. Consistent with the Culture and Behavior model that guided the research, the test of causal models based on the analysis of structural equations show that academic performance is in part a function of variations in the level of fatalism, directly as well as indirectly through its influence in the attribution processes and failure-related emotions. In general, the model representing the proposed structure of relations among fatalism, attributions, and emotions as determinants of academic performance fit the data for both Mapuche and non-Mapuche students. However, results show that some of the relations in the model are different for students from these two ethnic groups. Finally, according to the results from the analysis of causal models, family SES appear to be the most important determinant of fatalism.